The Effort of the United States (USA) of the Donald Trump Era to Promote the Denuclearization of North Korea, 2017-2020 - Al Furqan Iskandar Putra; Ali Maksum (Budapest International Research and Critics University, 2022)
This study analyzes the efforts of the United States in encouraging the denuclearization process of North Korea in 2017-2020. The United States as a Super Power country has an important role in overcoming the North Korean nuclear problem. As one of the countries with growing nuclear possessions, the international scope feels threatened, so efforts are needed to encourage North Korea to immediately denuclearize. Seeing this, the United States has made efforts that are considered to be able to encourage the denuclearization of North Korea. In this study, the author uses Strategies and Tactics in Negotiation in the form of Contending and Problem-solving strategies to see what efforts the United States has made in promoting the denuclearization of North Korea. Does this study answer why the United States (US) efforts in pushing for the 2017-2020 denuclearization of North Korea in the Donald Trump era failed?